Knockdown of Circ_0037658 Alleviates IL-1β-Induced Osteoarthritis Progression by Serving as a Sponge of miR-665 to Regulate ADAMTS5 - Li, Ningbo; Wang, Yongsheng; Wu, Xuejian (Frontiers in Genetics, 2022)
Background: Osteoarthritis (OA) is a chronic musculoskeletal degeneration disease, which brings great pain to patients and a tremendous burden on the world’s medical resources. Previous reports have indicated that circular RNAs (circRNAs) are involved in the pathogenesis of OA. The purpose of this study was to explore the role and mechanism of circ_0037658 in the OA cell model. Methods: The contents of interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) were measured using an enzyme-linked immunosorbent assay (ELISA). Cell proliferation ability and apoptosis were detected using Cell Counting Kit-8 (CCK-8), 5-ethynyl-2’-deoxyuridine (EDU), and flow cytometry assays. Western blot assay was used to measure the protein levels of Bcl-2 related X protein (Bax), Cleaved-caspase-3, MMP13, Aggrecan, and ADAMTS5. The expression of circ_0037658, microRNA-665 (miR-665), and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) 5 was detected using real-time quantitative polymerase chain reaction (RT-qPCR). Dual-luciferase reporter assay and RNA Immunoprecipitation (RIP) assay were manipulated to analyze the relationships of circ_0037658, miR-665, and ADAMTS5. Results: Human chondrocytes (CHON-001 cells) were treated with interleukin-1β (IL-1β) to establish an OA cell model. Circ_0037658 and ADAMTS5 levels were increased, and miR-665 was decreased in OA cartilage samples and IL-1β-treated chondrocyte cells. Moreover, circ_0037658 silencing promoted proliferation, and impaired inflammation, apoptosis, and ECM degradation in IL-1β-treated CHON-001 cells. Mechanically, circ_0037658 acted as a sponge of miR-665 to regulate ADAMTS5 expression. Conclusion: Circ_0037658 knockdown relieved IL-1β-triggered chondrocyte injury via regulating the miR-665/ADAMTS5 axis, promising an underlying therapeutic strategy for OA.